European security in transition - Hauser, Gunther 1968-; Kernic, Franz (Ashgate Publishing Limited, 2006)
Since the end of World War II, security and defense have played a major role in European politics. This volume provides an interdisciplinary look at the development and the status of the European security system as well as selected key issues on security agenda